A comparison of continuous, dense, and lean schedules of noncontingent access to matched competing stimuli to reduce stereotypy. (1st February 2022) - Llinas, Mary; Wilder, David A.; Walz, Ryan
Abstract: Noncontingent or response‐independent access to matched, competing stimuli has been shown to be effective to decrease automatically maintained challenging behavior. Despite research on its effectiveness, various schedules of noncontingent access to matched competing stimuli have not been directly compared. The purpose of the current study was to compare the effectiveness of and preference for continuous, dense (fixed‐time 30 s), and lean (fixed‐time 60 s) schedules of noncontingent access to matched competing stimuli to decrease automatically maintained stereotypy exhibited by two children with autism. We also conducted a within session analysis of the lean condition to examine possible mechanisms responsible for the effects of the procedure. The results showed that the continuous schedule was most effective and most preferred to reduce stereotypy for both participants. A social validity measure indicated that the participant's caregivers approved of and preferred the continuous schedule.